Phonon-mediated superconductivity in the metal diborides XB2 under pressure - Qiu, Zhi-Yuan; Li, Wen-Guang; Liu, Zheng-Tang; Liu, Qi-Jun (Physical chemistry chemical physics : PCCP, 2025)
As a promising candidate for high-temperature superconductors, the AlB2 structure has garnered significant attention. Notably, the discovery of MgB2, which is stable at zero pressure and exhibits a high Tc of 39 K, has sparked a surge in research on metal borides. Metals, acting as electron donors, play a crucial role in stabilizing the relative positions of metal and boron atoms, thereby contributing to the stabilization of the crystal structure and the enhancement of superconductivity. In this study, the Mg atom was replaced with another metal atom X (X = Li, Ca, Sc, Ti, V, Rb, Zr, Nb, Cs, Ba, Hf, Ta). The resulting 12 compounds demonstrated stability at zero or low pressure. However, none of these compounds exhibited superconductivity comparable to that of the parent MgB2. Among them, LiB2, CsB2, and RbB2 emerged as the most promising candidates for superconductors. These findings highlight the complex interplay between the density of electronic states at the Fermi level and electron–phonon coupling in determining the superconductivity of binary metal borides. The computational results provide valuable insights for future research and the design of new superconducting materials within this family of metal compounds.